Reduce NOx Emissions by Adsorber-Reduction Catalyst on Lean Burn Engine - Dongpeng Yue; Qing Chang; Lei Liu; Wen Zhang; Shaoshu Chen; Zhijun Li Zhijun Li (Universitas Ahmad Dahlan, 2013)
The effect of a new catalyst system composed of traditional three way catalyst converter and adsorber-reduction catalysis converter on the emission characteristics and BSFC (Breake Specific Fuel Consumption- BSFC)of a lean burn gasoline engine operated were investigated in this paper under different schemes of catalyst converter arrangement and different speeds and loads. The results show that the position of Three Way Catalyst is before the NOx adsorber Catalyst was the best scheme of catalyst converter arrangement. Which has the highest converter efficiency of reduction NOx emission in lean burn gasoline engine. The effects of speed on the exhaust emission and BSFC were also related to the ratio of lean burn time to rich burn time and the absolute value of both time of the adsorber-reduction catalyst converter. The load of the engine was the main influential factor to the exhaust emission characteristics and BSFC of lean burn gasoline engine, and the more load of the engine was, the more NOx emission, the less NOx conversion rate (CNOx) and the better BSFC were.